2021
DOI: 10.1017/s1431927621000039
|View full text |Cite
|
Sign up to set email alerts
|

Study on Evolution of Micropipes from Hexagonal Voids in 4H-SiC Crystals by Cathodoluminescence Imaging

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…In Case II (dark), the increase in the PL intensity of the N–B DAP originates from an increase in the RDA of C D−A [ 15 ]. Considering that the DAP recombination rate is an efficient measure of the emission luminescence [ 29 , 30 , 31 , 32 ], and the RDA is proportional to the donor concentration (C D ) and the acceptor concentration (C A ), the correlation between the C D , C A , and PL properties can be evaluated, as described previously [ 21 ]. The increased N–B DAP peak intensity for Case II was, therefore, attributed to an increase in C N .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Case II (dark), the increase in the PL intensity of the N–B DAP originates from an increase in the RDA of C D−A [ 15 ]. Considering that the DAP recombination rate is an efficient measure of the emission luminescence [ 29 , 30 , 31 , 32 ], and the RDA is proportional to the donor concentration (C D ) and the acceptor concentration (C A ), the correlation between the C D , C A , and PL properties can be evaluated, as described previously [ 21 ]. The increased N–B DAP peak intensity for Case II was, therefore, attributed to an increase in C N .…”
Section: Resultsmentioning
confidence: 99%
“…The increased N–B DAP peak intensity for Case II was, therefore, attributed to an increase in C N . Aukerman and Millea’s model [ 30 , 31 , 32 ] suggests that the correlation between DAP recombination and concentration causes the PL intensity to increase with an increase in the difference between C N and C B ; this is known as the N–B concentration gap. More specifically, when the N–B concentration gap is larger than C B , saturation occurs, whereas when the N–B concentration gap is more than twice C B , the PL emission intensity decreases due to the presence of non-radiative defects (non-emission), as evidenced in Case II [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…A unique transitional configuration of superscrew dislocations to closed-core elementary screw dislocations was proposed by Daisuke Nakamura et al, which showed good ability to explain the decrease of micropipe density during crystal growth [ 10 ]. Arora, Aman, et al used cathodoluminescence (CL) imaging technology to confirm that multiple micropipes could originate from a single hexagonal void, and energy-dispersive spectroscopy (EDS) showed that the inside of the micropipe walls exhibited higher levels of carbon [ 11 ]. However, some research questions on micropipes have yet to be successfully examined.…”
Section: Introductionmentioning
confidence: 99%